The Effect of Locations of Study and Region of Birth on Immigrants' Wages - Anam, Amani (Université d'Ottawa | University of Ottawa, 2017)
This paper uses the 2006 Canadian Census and the 2011 National Household Survey to examine the impact of location of study, place of birth, and the assimilation rate on immigrants’ earnings in the Canadian labour market, while taking year and geographic fixed effects into account. The paper finds that immigrants who studied outside of Canada, the U.S., or Europe incur a significant negative wage impact of approximately 10% on average. Specifically, the negative impact is 7% for men and 15% for women. With respect to place of birth, immigrants face negative entry effects, even if they were born in other Western countries. The largest negative premiums were present for immigrants from Asia. In some regions, women have a smaller disadvantage with respect to their place of birth; however, in many Asian countries, there is a considerable difference between earnings for women and men. Furthermore, when the effect of immigrants’ Canadian work experience and foreign work experience are examined separately, foreign work experience is shown to have a very small return.